2016
DOI: 10.1049/iet-nbt.2016.0007
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of sol–gel method synthesised MgZnFe 2 O 4 nanoparticles and its cytotoxic effects on breast cancer cell line, MDA MB‐231 in vitro

Abstract: In this study, nanocrystalline magnesium zinc ferrite nanoparticles were successfully prepared by a simple sol-gel method using copper nitrate and ferric nitrate as raw materials. The calcined samples were characterised by differential thermal analysis/thermogravimetric analysis, Fourier transform infrared spectroscopy and X-ray diffraction. Transmission electron microscopy revealed that the average particle size of the calcined sample was in a range of 17-41 nm with an average of 29 nm and has spherical size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…So far, many investigations were done based on metallic nanoparticles (metal oxides, metallic nanocomposites, magnetic nanoparticles, graphene‐based nanoparticles etc.) to find out effective anticancer drugs that play an important role in the apoptosis [ 72 , 73 , 74 , 75 , 76 , 77 ]. The presence of anionic phospholipids in cancer cells causes negative zeta potential that absorb into positively charged nanoparticles by strong electrostatic interaction [ 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…So far, many investigations were done based on metallic nanoparticles (metal oxides, metallic nanocomposites, magnetic nanoparticles, graphene‐based nanoparticles etc.) to find out effective anticancer drugs that play an important role in the apoptosis [ 72 , 73 , 74 , 75 , 76 , 77 ]. The presence of anionic phospholipids in cancer cells causes negative zeta potential that absorb into positively charged nanoparticles by strong electrostatic interaction [ 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nordin et al. investigated the cytotoxic potential of sol‐gel derived MgZn ferrite against breast cancer cell line (MDA‐MB‐231) with concentration ranging 0–800 μg/mL and observed higher IC 50 (=500 μg/mL) than that of the present result (IC 50 =72.12 μg/mL) [43] . Nigam et al.…”
Section: Resultsmentioning
confidence: 56%
“…[42] Nordin et al investigated the cytotoxic potential of sol-gel derived MgZn ferrite against breast cancer cell line (MDA-MB-231) with concentration ranging 0-800 μg/mL and observed higher IC 50 (= 500 μg/mL) than that of the present result (IC 50 = 72.12 μg/mL). [43] Nigam et al also reported a series of zinc doped magnesium ferrites derived using sol-gel method and conducted their anticancerous study against breast cancer cell line (MCF-7) and showed low response at lower concentrations (50 μg/mL and 100 μg/ mL), [44] whereas in the present findings biosynthesized OBLE@MgÀ Zn NPs showed potent cytotoxic potential at lower concentrations. Table 3 illustrates the comparative analysis of…”
Section: Cytotoxic Activitymentioning
confidence: 45%
“…The universal formulary A x B (1−x) Fe 2 O 4 , where “A” and “B” both are divalent transition ions. The MgZnFe 2 O 4 is fundamentally a dual oxide arrangement (MgO–ZnO–Fe 2 O 2 ) that has maybe applicable as absorbents, semiconductors, and catalysts 26 . In original form, and Fe 2 O 4 is a dielectric insulator, and MgO and ZnO are p-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%